Corrigendum: “Equilibrium leaching of selected ultraviolet stabilizers from plastic products” (Journal of Hazardous Materials (2022) 427, (128144), (S0304389421031149), (10.1016/j.jhazmat.2021.128144)) - Do, Anh T.Ngoc; Ha, Yeonjeong; Kang, Hyun Joong; Kim, Ju Min; Kwon, Jung Hwan (Journal of Hazardous Materials, 2022)
The Authors would like to correct the following inadvertent errors. In the Supplementary Material of the earlier published article, a mistakenly drew chemical structure of UV328 was used due to author careless. The chemical structure of UV328 should be replaced by the correct one presented herewith the tert-pentyl groups instead of tert-butyl groups (Row 4 of Table S1 in the corrigendum file). In addition, the Kow values, which were obtained from EPI Suite™4.11 (EPA, 2012) have been also replaced with its correct version because of typing mistakes. We have corrected Table S1 (in Supplementary Material) as shown below. This correction does not influence the results and discussion of the original article. The authors would like to apologize for any inconvenience caused.